PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS VII NEGERI 8 PADANG - Nursaid, Ade Darma Putra, Abdurahman, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study is (1) to describe the text short story writing skills of students of class VII SMP Negeri 8 Padang before and after using cooperative learning model Think Talk Write aided media beamed images. (2) analyze the effect of the use of cooperative learning model Think Talk Write aided media beamed images to text short story writing skills of students of class VII SMP Negeri 8 Padang. This research is a quantitative study with experimental method. The results of this research there are three: (1) The text of the short story writing skills of students of class VII SMP Negeri 8 Padang before using cooperative learning model Think Talk Write aided media beamed images that are in the qualification More than Enough (LDC). (2) The text of the short story writing skills of students of class VII SMP Negeri 8 Padang after using cooperative learning model Think Talk Write aided media beamed images that are in the qualification Good (B). (3) based on the t-test, the alternative hypothesis (H1) is accepted on the confidence level and degrees of freedom (df) = n - 2 for thitung> ttable. Based on the findings, it was concluded that cooperative learning model Think Talk Write aided media beamed images can be used as an alternative in the teaching of writing short story text.Â Kata kunci: pengaruh, kooperatif tipe influence, Â think talk write, media gambar berseri, menulis cerita pendek.